Violence against pregnant women in the experience of the rape centre of Turin: Clinical and forensic evaluation. (November 2020) - Bo, Marco; Canavese, Antonella; Magnano, Laura; Rondana, Alice; Castagna, Paola; Gino, Sarah
Abstract: Pregnant women can be victims of violence: as a matter of fact, far from being a protective factor, pregnancy can trigger or worsen episodes of abuse. Studies conducted by the WHO highlight that its incidence fluctuates between 1% and 28%. Therefore violence during pregnancy is endemic all over the world and involves all social strata. We analysed 113 medical records concerning pregnant women (average age 27.9 ± 6.0 years, 80 foreigners), who turned to the Centro Soccorso Violenza Sessuale, one of the two Italian Rape Centre, in Turin between January 1st, 2005 and December 31st, 2017. Fifty-three women were visited in the first trimester, 41 in the second, and 16 in the third, while 3 during the puerperium. The current partner was accused to be the abuser by the 84.4% of the Italian women and by the 69.2% of the foreigners. Sixty-eight women suffered multiple forms of violence, while 98 suffered only physical violence, and 3 reported only sexual abuse. According to 20 women, violent episodes increased during pregnancy. The clinical history of these women was characterized by some recurrent physical symptoms, such as pelvic pain, abdominal pain, facial pain and headache and 54 women presented injuries (abrasions and ecchymosis). Our results confirm that violence in pregnancy is a social and public health problem. Therefore it is important that the health personnel should be prepared not only to care for women seeking help, but above all its better preparation could also identify victims of violence, which do not report abuse. Highlights: Increasing trend in the number of pregnant women annually examined. Half of pregnant women suffered multiple form of violence. No clear evidence about pregnancy as a trigger for violent episodes. More than a quarter of pregnant women opted for a voluntary abortion. The abuser is usually the actual or a previous partner.